Selectivity of flame-spray-made Nb/ZnO thick films towards NO 2 gas - Viruntachar Kruefu (2018)
Unloaded ZnO and Nb/ZnO nanoparticles containing 0.25, 0.5 and 1 mol.% Nb were produced in a single step by flame-spray pyrolysis (FSP) technique. The nanoparticles were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The BET surface area (SSABET) of the nanoparticles was measured by nitrogen adsorption. FSP yielded small Nb particles attached to the surface of the supporting ZnO nanoparticles, indicating a high SSABET. The morphology and accurate size of the primary particles were further investigated by TEM. Nb/ZnO nanoparticles paste composed of ethyl cellulose and terpineol as binder and solvent respectively was coated on Al2O3substrate interdigitated with gold electrodes to form thick films by spin coating technique. After the sensing tests, the morphology and the cross-section of sensing film were analyzed by SEM and EDS analyses. The influence on a low dynamic range of Nb concentration on NO2response (0.1-4 ppm) of thick film sensor elements was studied at the operating temperatures ranging from 250 to 350 °C in the presence of dry air. The optimum Nb concentration was found be 0.5 mol.% and 0.5 mol.% Nb exhibited an optimum NO2response of ∼1640 and a short response time (27 s) for NO2concentration of 4 ppm at 300 °C. © 2011 Elsevier B.V.